2012
DOI: 10.1155/2012/162729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Short-Term Steel Corrosion Products Formed in Tropical Marine Environments of Panama

Abstract: A low-carbon steel A-36 and two conventional weathering steels A-588 and COR-420 exposed at four atmospheric test stations located in (i) Tocumen, an urban site near the Pacific Ocean, (ii) Sherman-Open, (iii) Sherman-Coastal, and (iv) Sherman-Breakwater on the Caribbean coast of Panama. Kinetics of the short-term atmospheric corrosion process and the relationship with exposure time and environmental characteristics of each site were investigated. The atmospheric exposure conditions, particularly the time of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…Previous studies reported that n > 0.5 indicates a nonprotective rust layer, while n < 0.5 designates a protective rust layer . Another interpretation of the n value is the change of CR at a longer exposure time . For n > 1, CR is accelerated with time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that n > 0.5 indicates a nonprotective rust layer, while n < 0.5 designates a protective rust layer . Another interpretation of the n value is the change of CR at a longer exposure time . For n > 1, CR is accelerated with time.…”
Section: Resultsmentioning
confidence: 99%
“…The content of goethite was comparable at both stations. In Panama, low‐carbon steel and weathering steels were subjected to tropical‐coastal zones of Pacific Ocean and Caribbean Sea. Airborne pollutions and total TOW were monitored during dry and rainy seasons separately, indicating the wash effect of rain.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-FeOOH has been identied as corrosion product which was further conrmed through conversion electron Mössbauer spectroscopy (CEMS). Corrosion products of carbon steel (A-36) and weathering steels (A-588 and COR 420) were analysed for atmospheric corrosion through FTIR by Jaen et al 141 The authors conrmed the presence of gamma and alpha-FeOOH, which has been further conrmed through other analytical techniques, such as XRD and Mössbauer spectroscopy. Recently, Chong et al 142 used the synergistic effect of imidazolinium and 4-hydroxycinnamate (organic salt) for corrosion inhibition of mild steel in 0.1 M NaCl and FTIR analysis conrmed the interaction between mild steel surface and 4hydroxycinnamate.…”
Section: Conventional Characterization Techniquesmentioning
confidence: 99%
“…Among them, the yellow product was mainly composed of a-FeOOH and g-FeOOH. 29,30 This indicated that WBE was prone to corrosion seriously within eight hours. However, from Fig.…”
Section: Corrosion Morphologymentioning
confidence: 97%